Assessment of System Development and Business Process Reengineering - Anbazhagan, Dr.A. (International Journal of Advanced Science and Technology, 2019)
The present study aims to evaluate the assessment of system development and business process reengineering.Business Process Reengineering (BPR) is the fundamental rethinking and radical redesign of business processes to achieve dramatic improvements in critical, contemporary measures of performance, such as cost, quality, service and speed.” The random sampling method was used to select the samples. 100 samples were selected. The statistical test such as t-test, F-test and correlation were used. The statistical result proved that there is a significant relationship between business process reengineering and different method. Further technology increased the level of business process reengineering.Therefore it is concluded that traditional organization is that which follows traditional rules, using traditional hierarchical structures and control systems and applying information technology for supporting their activities within those structures. A modern organization, on the other hand, is customer focused, process-based, and using IT as an enabling factor for organizational change and the gain of competitive advantage . Keyword:. System development, business, process, re-engineering